2020
DOI: 10.18502/jovr.v15i1.5946
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal Thickness in Acute Non-arteritic Anterior Ischemic Optic Neuropathy

Abstract: Purpose: To compare the choroidal thickness in eyes with acute non-arteritic anterior ischemic optic neuropathy (NAION) with healthy contralateral eye and normal controls. Methods: Thirty-eight eyes with NAION, thirty-eight unaffected fellow eyes, and seventy four eyes from 37 healthy, age- and sex-matched subjects were included in this prospective comparative case-control study. Choroidal thickness was measured by enhanced depth imaging (EDI) of spectral domain optical coherence tomography (SDOCT). Peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…However, the accuracy of depicting choroid layer declined in the extremely thick group in this study, a finding that has also been previously reported. Ophthalmologists have put focus on pathophysiology between choroid layer and various ocular diseases ranging from anterior segment (keratoconus, glaucoma) to posterior segment (AMD, PCV, optic neuropathy) [29][30][31][32][33][34]. Through the experimental thirty cases in our study, the feasibility of this Mask R-CNN model has been proved.…”
Section: Discussionmentioning
confidence: 83%
“…However, the accuracy of depicting choroid layer declined in the extremely thick group in this study, a finding that has also been previously reported. Ophthalmologists have put focus on pathophysiology between choroid layer and various ocular diseases ranging from anterior segment (keratoconus, glaucoma) to posterior segment (AMD, PCV, optic neuropathy) [29][30][31][32][33][34]. Through the experimental thirty cases in our study, the feasibility of this Mask R-CNN model has been proved.…”
Section: Discussionmentioning
confidence: 83%
“…For supra-physiological levels of choroidal expansion, we estimated choroidal volume of 32 and 35 uL based on the choroidal thickness observed in subjects with NAION. 4 , 27 In brief, we used choroidal thicknesses that were reported at locations from 100 µm to 3000 µm starting at the scleral canal opening of eyes affected by NAION. 4 , 27 We then estimated the degree of choroidal expansion as the difference in choroidal volume between healthy subjects and subjects with NAION.…”
Section: Methodsmentioning
confidence: 99%
“…It plays an important role in various vision deteriorating diseases such as age related macular degeneration, choroidal neo-vascularization, central serous chorioretinopathy and chorioretinal atrophy in high myopia. 1,2 Choroidal thickness is determined by amount of vascularization and varies by age, sex, refractive state of eye along with any previous history of ocular trauma or surgery like cataract extraction. [3][4][5] Phacoemulsification is most common invasive intraocular surgery for removal of cataract and improves visual outcome markedly.…”
Section: Introductionmentioning
confidence: 99%